2022
DOI: 10.1155/2022/2734490
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Type 1 Diabetes: Circulating MicroRNA Expression Profiles Changes from Preclinical to Overt Disease

Abstract: Aims/Hypothesis. The role of microRNAs (miRNAs) in type 1 diabetes (T1D) pathogenesis and progression has been described but remains elusive. Objectives. To evaluate the potential biological involvement of miRNA expression in the immune response and beta cell function in T1D. Methods.We screened 377 serum miRNAs of 110 subjects divided into four groups: healthy individuals (control group) and patients at different stages of T1D progression, from the initial immunological manifestation presenting islet autoanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…CCND2 [1083], VCAM1 [761], PDGFB (platelet derived growth factor subunit B) [1059], PTCH1 [1098], FOXQ1 [1044], IGF2BP1 [1162], ACTC1 [1192], DAPK1 [947], hsa-mir-2110 [1676], hsa-mir-10b-5p [1677], TCF3 [1678], NR1I2 [1679] and TRIM28 [1680] have been shown to be associated with inflammation. Studies have shown that CCND2 [1495], VCAM1 [1462], PTPRD (protein tyrosine phosphatase receptor type D) [1496], PRKCB (protein kinase C beta) [1476], IGF2BP1 [1545], hsa-mir-200a-3p [1681] and hsa-mir-10b-5p [1682] are an important biomarkers of diabetes mellitus. VCAM1 [110], PDGFB (platelet derived growth factor subunit B) [121], IGF2BP1 [162], DAPK1 [183] and hsa-mir-17-5p [1683] are a potential markers for the detection and prognosis of endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…CCND2 [1083], VCAM1 [761], PDGFB (platelet derived growth factor subunit B) [1059], PTCH1 [1098], FOXQ1 [1044], IGF2BP1 [1162], ACTC1 [1192], DAPK1 [947], hsa-mir-2110 [1676], hsa-mir-10b-5p [1677], TCF3 [1678], NR1I2 [1679] and TRIM28 [1680] have been shown to be associated with inflammation. Studies have shown that CCND2 [1495], VCAM1 [1462], PTPRD (protein tyrosine phosphatase receptor type D) [1496], PRKCB (protein kinase C beta) [1476], IGF2BP1 [1545], hsa-mir-200a-3p [1681] and hsa-mir-10b-5p [1682] are an important biomarkers of diabetes mellitus. VCAM1 [110], PDGFB (platelet derived growth factor subunit B) [121], IGF2BP1 [162], DAPK1 [183] and hsa-mir-17-5p [1683] are a potential markers for the detection and prognosis of endometriosis.…”
Section: Discussionmentioning
confidence: 99%